STUDY OF SOME PHYSIOLOGICAL AND HISTOLOGICAL CHANGES IN MUS MUSCULUS MICE AFTER EXPOSURE TO CHLORPYRPHOS PESTICIDE - Majdy F. Majeed AL-Ali; Nowfel H. Jassim (Basrah Journal of Veterinary Research)
The aim of this study to determinate the toxic effect for different concentrations of organphosphorous pesticide called Chlorpyrphous, some histological and physiological features of the internal organs of ( Mus musculus ) mice by oral administration. The experimental mice were oral administration of (0.1mg.kg and 0.2 mg /kg. ) twice weekly during 3 weeks. After 21 day of experiment the (GOT, GPT )enzymes and urea and total protein were estimated . The following organ were taken for histological studies: liver, kidney, lung, stomach, intestine, and testes. The histological studies were carried out on the liver and kidney. The results of this study showed that the oral administration of chloropyrphose in some histological changes in kidney and liver. and elevation in the level of GOT of GPT enzyme also urea and protein.